Priority challenges and critical success factors for GIS in Al-Mansour Municipality - Raheem Younis Alazzawi, Firas (International Journal of Psychosocial Rehabilitation, 2020)
This paper looks at the practical use of geographic information systems for municipal service development. CSFs also discuss, in particular, the difficulties of GIS implementation in order to assist in improving municipal services provided by Al-Mansour municipality. This allows GIS to provide single-service network information on destinations. For example, maps and geographical location details, property, roads, green areas, water networks, and sewage networks are available, etc. GIS also offers a catalog of future service operations and existing municipal procedures. This centralized knowledge network will facilitate public services and help make decisions for managers in the future. This paper discusses CSFs and the obstacles to be faced in order to obtain GIS ability effectively. The critical contribution of this research is to establish a GIS challenge registry. The problems proposed were grouped into four critical combinations with other sub-fabrics for the characteristics of GIS as an information system. Challenges include HR (top management support, GIS experience, GIS training), data (i.e., data availability, quality of data, and maximum data protection), and software and hardware (i.e., use of suitable technology, quality software, and hardware). (i.e., sufficiently organized and prepared efforts) and enough assistance.